2020
DOI: 10.1136/thoraxjnl-2019-214307
|View full text |Cite
|
Sign up to set email alerts
|

Duration of neonatal oxygen supplementation, erythropoiesis and blood pressure in young adults born preterm

Abstract: BackgroundAlthough erythropoiesis is impaired and anaemia frequent in neonates born preterm, haematopoiesis in adults born preterm has not been previously studied.ObjectiveWe, thus, aimed to evaluate haemoglobin and erythropoietin levels in young adults born preterm, to identify neonatal events associated with erythropoiesis in adulthood and to examine the relationships of haemoglobin levels with respiratory function and blood pressure.MethodsWe assessed a cohort of 101 young adults (ages 18–29) born preterm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Future work should determine uncoupling protein expression and oxidative stress generation in adults born preterm, and may provide further pathophysiologic basis for the increased risk of diseases associated with oxidative stress. Preterm-born adults also had higher hemoglobin levels, which have been described in prior studies despite normal erythropoietin levels ( 29 ). It is possible that higher global mitochondrial oxygen consumption contributes indirectly to the higher hemoglobin levels, though we did not find evidence of direct correlation between PBMC respiration and hemoglobin.…”
Section: Discussionsupporting
confidence: 67%
“…Future work should determine uncoupling protein expression and oxidative stress generation in adults born preterm, and may provide further pathophysiologic basis for the increased risk of diseases associated with oxidative stress. Preterm-born adults also had higher hemoglobin levels, which have been described in prior studies despite normal erythropoietin levels ( 29 ). It is possible that higher global mitochondrial oxygen consumption contributes indirectly to the higher hemoglobin levels, though we did not find evidence of direct correlation between PBMC respiration and hemoglobin.…”
Section: Discussionsupporting
confidence: 67%
“…Studies of children and adults born very or extremely preterm have shown that preterm birth is associated with altered nephrogenesis and smaller kidneys, with the reduction in kidney size correlating with higher blood pressure in adults. 53 Studies have also shown higher hemoglobin, 54 evidence of sympathetic nervous autonomic system activation, 55 and hypothalamus-pituitary-adrenal dysregulation 56 in preterm-born adults, which all potentially contribute to higher blood pressure. A recent study of 101 young adults born on average at 27 weeks’ gestation compared with 105 young adults born at term found no association between preterm birth and markers of inflammation and oxidative stress, as well as no association between high blood pressure and other cardiovascular risk factors (such as glucose intolerance, which is also more prevalent in preterm-born individuals), suggesting a unique mechanism to hypertension and disease development.…”
Section: Late Sequelae and Future Cardiovascular Disease Riskmentioning
confidence: 99%
“…Infants born very preterm (< 32 weeks of gestation) exhibit alterations in right ventricular (RV) function that persist through infancy and which are aggravated in the presence of bronchopulmonary dysplasia (BPD), a pulmonary complication of very preterm birth. 13 Adults born preterm also exhibit alterations in RV structure and function, [14][15][16] in addition to higher rates of obstructive lung disease 17,18 and pulmonary vascular disease. [19][20][21] Whether the deleterious impact of BPD on RV function persists later in life, however, remains to be determined.…”
mentioning
confidence: 99%